Board gender diversity, corporate governance, and earnings management: Evidence from an emerging market. Issue 1 (6th December 2019) - Orazalin, Nurlan
Abstract : Purpose: The purpose of this study is to examine whether board gender diversity and other board characteristics affect earnings management practices of top public companies in Kazakhstan. Design/methodology/approach: The study analyzes data of top public companies for the period 2010-2016. Data on corporate governance were manually collected from annual reports and investment memorandums, and financial data were collected from audited financial statements. Findings: The empirical results show that companies with greater board gender diversity are more effective in constraining earnings management. The findings also indicate that companies with larger boards adopt a more restrained approach to earnings management practices, thus supporting the theoretical framework of the study. However, the results provide weak evidence of the association between board independence and earnings quality. Originality/value: This study is the first to investigate the relationship between gender diversity and earnings management in emerging markets such as Kazakhstan that offers managerial and policy implications.